2012
DOI: 10.1519/jsc.0b013e318234e8a0
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Speed Training Protocols on Sprint Acceleration Kinematics and Muscle Strength and Power in Field Sport Athletes

Abstract: A variety of resistance training interventions are used to improve field sport acceleration (e.g., free sprinting, weights, plyometrics, resisted sprinting). The effects these protocols have on acceleration performance and components of sprint technique have not been clearly defined in the literature. This study assessed 4 common protocols (free sprint training [FST], weight training [WT], plyometric training [PT], and resisted sprint training [RST]) for changes in acceleration kinematics, power, and strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
141
4
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(177 citation statements)
references
References 13 publications
13
141
4
8
Order By: Relevance
“…6v6 SSGs) (Hill-Haas et al, 2009). The inherent structure of the 12-player SST drill is more reflective of traditional sprint acceleration training, which tends to feature longer recovery periods between sprint efforts (Lockie et al, 2014a, Lockie et al, 2012, Spinks et al, 2007). An SST drill that features more players could potentially be used to target maximal sprint acceleration and direction changes, as longer recovery periods between high-intensity efforts could assist with attenuation the effects of fatigue decreasing performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6v6 SSGs) (Hill-Haas et al, 2009). The inherent structure of the 12-player SST drill is more reflective of traditional sprint acceleration training, which tends to feature longer recovery periods between sprint efforts (Lockie et al, 2014a, Lockie et al, 2012, Spinks et al, 2007). An SST drill that features more players could potentially be used to target maximal sprint acceleration and direction changes, as longer recovery periods between high-intensity efforts could assist with attenuation the effects of fatigue decreasing performance.…”
Section: Discussionmentioning
confidence: 99%
“…The study occurred during the participants' competition season (Jovanovic et al, 2011, Lockie et al, 2012, Lockie et al, 2014b, Spinks et al, 2007, and they continued their existing physical activity during the study, which generally consisted of 2-3 field-and 1-2 gym-based sessions, and one game, per week. Participants were notified of the research procedures, requirements, benefits, and risks of participation, before providing written informed consent.…”
Section: Participantsmentioning
confidence: 99%
“…Sports specialist literature reveals that rugby is used for a variety of tests that measure the ability of the players and the motor default level of specific physical training. This makes it impossible to compare results obtained in previous studies by other authors (Johnston & Gabbet, 2011;Lockie, Murphy, Schultz, Knight, & de Jonge, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have reported the effects of resisted sprint training to increase sprint speed in the early part of and during the acceleration phase [7][8][9][10][11][12][13][14]. The acute effects of this type of training are decreased stride length, increased trunk angle (the angle between the trunk and the vertical axis during sprint) and increased step frequency [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…joint angle, stride length) were recognized to improve sprint speed in the early part of the acceleration phase [7-10, 12, 14]. Several previous studies on resisted sprint training focused on approximately 13% body mass loading to minimize loss of sprint specificity [8,10,11,17,18]. On the other hand, another study instead used a load based on the degree of decreasing sprint speed [9].…”
Section: Introductionmentioning
confidence: 99%